The Measure of Frequency and Correlations of DASS-21 among Students of the Education Faculty - Ghulam Haidar Ghulami; Mohammad Qasim Noori; Qasim Joya (Journal of Psychology and Behavior Studies, 2025)
The primary aim of this study was to determine the prevalence of depression, anxiety, and stress among students of the Faculty of Education at Baghlan University. In addition, the research sought to examine the correlations between these psychological variables. The sample population included students from the first and second semesters, and out of a total of 126 students, 100 voluntarily agreed to participate in the study.The findings revealed that a significant proportion of the students exhibited high levels of depression, anxiety, and stress. Furthermore, statistical analyses indicated a moderate and positive correlation among the three variables. This suggests that an increase in one of these emotional states is likely to be associated with increases in the others. These results highlight the urgent need for psychological support and preventive interventions within the academic environment.